Studi Pengelolaan Limbah Industri Tempe Rumah Tangga Di Kota Salatiga dan Kabupaten Semarang: Permasalahan, Dampak, Dan Alternatif Solusi Berkelanjutan - Muhammad Fadel Suryaputra; Indri Sulfazanah; Nisrina Hasna Tsabitha; Yumna Khairunnisa; Farah Bidara (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: Most home-based tempeh producers still apply traditional methods without proper business documentation and lack adequate wastewater treatment, causing liquid waste to flow directly into nearby waters. This condition threatens environmental quality. The study focuses on examining waste management practices in the home-based tempeh industry within Salatiga City and surrounding areas. Methods: This study employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and document analysis. Data analysis followed the Miles and Huberman model, which consists of data reduction, data display also conclusion drawing and verification. The analysis process was conducted thematically by grouping information into categories such as types of waste, management methods, challenges faced, environmental awareness levels, and sustainable solution efforts. These categories were applied to two research areas, namely Salatiga and Semarang, providing a clear picture of waste management conditions in each location. This analytical structure enabled the researcher to systematically identify patterns, issues, and potential improvements. Result: The research revealed that many industry players still lack wastewater treatment systems, discharging liquid waste directly into waterways. Solid by-products, such as soybean skins, are often reused as animal feed, while organic-rich liquid waste threatens environmental health. Limited knowledge, land constraints, and high costs hinder treatment plant development. The study recommends simple measures like anaerobic biofilters and utilizing liquid waste as organic fertilizer to encourage sustainability and minimize environmental damage. Conclusion: Waste handling in Salatiga’s household tempeh industry remains basic, with liquid waste directly released into the environment. While solid waste is reused as animal feed, no sustainable system exists. Reducing pollution and promoting sustainability require training, technical guidance, and the adoption of simple wastewater treatment technologies